2017
DOI: 10.1111/pin.12506
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of Phenotypic Expression in Differentiated‐type Early Adenocarcinoma of the Stomach

Abstract: A total of 313 cases of differentiated-type early gastric adenocarcinomas, including 113 cases of small-sized carcinoma (5< × ≤10 mm) and 121 cases of microcarcinoma (0< × ≤5 mm), were examined immunohistochemically to clarify the phenotypic expressions. They were classified into four categories (gastric phenotype (G-type), intestinal phenotype, gastrointestinal phenotype, and null phenotype) by a two-step process: the phenotype based on an immunoprofile of mucin core proteins (MUCs) with CDX2 (w/.CDX2-assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Gastric cancer mucin phenotypes, categorized into intestinal, gastric, combined, and unclassified types based on the expression of these markers, have varied implications for malignancy [18]. Notably, gastric-type mucin phenotypes are critical to identify due to their increased malignant potential in early invasion and metastasis stages [19]. Abnormal expression or absence of mucin distribution can signal abnormal differentiation and maturation of gastric mucosal glands, serving as a molecular marker for malignant malignancy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer mucin phenotypes, categorized into intestinal, gastric, combined, and unclassified types based on the expression of these markers, have varied implications for malignancy [18]. Notably, gastric-type mucin phenotypes are critical to identify due to their increased malignant potential in early invasion and metastasis stages [19]. Abnormal expression or absence of mucin distribution can signal abnormal differentiation and maturation of gastric mucosal glands, serving as a molecular marker for malignant malignancy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…CDX2 is an intestine-specific transcription factor that is reportedly important for development and maintenance of the intestinal epithelium 4 , being closely associated with intestinal phenotypic expression in human gastric carcinomas and intestinal metaplasia 8 9 10 11 12 13 14 15 . In addition, it has been reported that CDX2 has both tumor suppressor 10 11 12 13 14 15 and oncogenic activities 14 , although it remains unclear whether it has an oncogenic role in gastric carcinogenesis. Furthermore, CDX2 is a more sensitive marker than MUC2 or CD10 for assessing presence of an intestinal phenotype from the very early stage of carcinogenesis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CDX2 is a more sensitive marker than MUC2 or CD10 for assessing presence of an intestinal phenotype from the very early stage of carcinogenesis 9 . Hayakawa et al reported that CDX2 expression was evident in 89.1 % of 313 cases of intestinal-type (by Lauren’s classification 16 ) early gastric adenocarcinoma 10 . In the current study, CDX2 expression was observed in 95 % (40 of 42) of cases, thus supporting its relationship to oncogenic activity in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the incidence of differentiated ECG foveolar-phenotype (DEGC) appears to be 7.9%–23.9% 11. Gastric-type mucin phenotypes should be distinguished from the other DEGC types because of their increased malignant potential in the incipient phases of invasion and metastasis 12. Early foveolar-phenotype differentiated adenocarcinomas tend to be significantly larger tumors and exhibit higher rates of submucosal invasion than the intestinal-phenotype 13.…”
Section: Introductionmentioning
confidence: 99%